PERCEPTION OF RISK TO COVID-19 FROM A MODELED EXERCISE OF METHODOLOGY, GNOSEOLOGY AND EPISTEMOLOGY IN POSTGRADUATE EDUCATION - Argota-Pérez, George (2021)
The aim of the study was to describe the perception of risk before COVID-19 from a modeling exercise of methodology, gnoseology and epistemology in postgraduate teaching. The study was carried out in July 2020 with university professors from the International Diploma ¨Strategic competence in scientific research methodology¨, which was developed at the San Luis Gonzaga National University in Ica, Peru. The qualitative observation and participation technique was applied to the university teachers, where an analysis of the route through some main avenues of the city of Ica was shown from 09:30 to 11:00 and 14:00 to 15:30. Through a random probability sampling, the number of people with the incorrect use of the mask as the main means of protection and biosafety against COVID-19 was recorded. Limitation was observed in the perception of risk of university teachers where there were no statistically significant differences between them. It is concluded that, from a modeled exercise that combines methodological, epistemological and epistemological aspects, the theory of motivation was used from a study context, but no other study is found where it is developed from hermeneutics and university training training, to contribute to increasing the perception of risk in the face of the COVID-19 pandemic.